Comparative Analysis of User Interface Design in Cognitive Behavioral Therapy (CBT) Mobile Applications for Pre-Elderly Users - Hanna Sofia Napitupulu; Irfansyah Irfansyah (Gorga : Jurnal Seni Rupa, 2025)
User Interface design plays a crucial role in supporting the effectiveness of digital Cognitive Behavioral Therapy (CBT) interventions based on mobile applications, especially for pre-elderly users who might have cognitive, visual, and motor limitations. This study aims to analyze and specifically compare the interface design of two popular CBT mobile applications, namely CBT Companion and Unstuck, based on Graphical User Interface (GUI) principles that focus on aspects of readability, consistency, navigation, and visual clarity. The method used was visual observation and descriptive analysis of GUI elements, including layout, color and contrast, typography, icons and symbols, as well as animation and transition. The analysis was conducted by considering the needs and characteristics of pre-elderly users based on related literature. The results showed that the Unstuck app was superior in visual consistency, typographic legibility, and linear navigation structure, making it more friendly to the limitations of pre-elderly users. In contrast, CBT Companion has a therapeutic visual approach but faces barriers in readability, layout inconsistency, and low colour contrast for readability. This study confirms that the effectiveness of digital CBT interventions is not only determined by the interventions’ content delivered but also by the interface design that can support the overall user experience. The implications of these findings emphasise the importance of applying inclusive design principles in the development of digital mental health applications for pre-elderly users.